ABOUT THE ARCHERY TERMS AND THE WORDS “yük - yü?” USED IN DİVÂNU LUGÂTİ'T-TÜRK - İlhan UÇAR (Fırat University, 2019)
One of the memorial works of 11th century Divânu Lugâti't-Türk is a significant work in terms of arrow and archery as it is in many other fields. Despite being a war instrument, Prophet Mohammed’s mentioning bow in his many quotes made arrow gain a religious importance. Besides, it is known that arrow has been used as an entertainment tool for centuries. Both arrow and archery has had an important position in Turk states being established throughout history. There are a lot of words about bow and archery in Divânu Lugâti't-Türk. Some of those are “azak, azuk, bagır, bagırlamak, başak, borı, çırguy, çuram, karvı, kesme, kiriş, kiş, kiş kurugluk, kurman, kuruglug ok, okçı, okluk, oktam, oktaş, toz, ya, yeten”. Some of these words are still being used due to the fact that traditional Turkish archery has been considered as a cultural heritage and passed down from generation to generation. The terms such as “yük” and “yü?” appear in some current resources covering issues about archery as do the words; bow, breast bow, quiver, and archer. However, there are some misconceptions in the usage of these two words in Divânu Lugâti't-Türk and the other sources. Misinterpretations of these two words “yük” and “yü?” which also take place in "Tarama Sözlüğü" (A kind of Turkish Dictionary) have led to ambiguities. In “Tarama Sözlüğü”, “yük” means fetus, embryo in the womb and “yü?” means feather of a bird. For this reason, as “ yü? of the arrow” and “yük of arrow” means quite differently and there occurs an opposition of meaning between the words “yü?” which is used to mean to put feather of a bird or a vest onto an arrow and “yük” meaning to increase the weight of an arrow. In this article, the terms about archery used in Divânu Lugâti't-Türk, the well-known work of Kâşgarlı Mahmud are going to be analyzed and the differences and misconceptions of the terms “yü?” and “yük” are going to be presented.